Comparison of single and multi-coolant axial jets on the temperature reduction of nose cone with multiple-row disk - Seyyed Amirreza Abdollahi; Iman Shiryanpoor; Ali Hosin Alibak; Seyyed Faramarz Ranjbar (Results in Engineering, 2023)
Ensuring the thermal safety of the nose cone on high-velocity shuttles is crucial for maintaining the overall safety of hypervelocity vehicles. This study investigated the use of axial single and multiple jets to reduce the thermal loading on the main structure of the nose cone, specifically through the implementation of a multi-row disk. The research focused on analyzing the flow structure and shock interaction near the spike assembly by introducing a coolant sonic jet. Computational fluid dynamics was employed to simulate the compressible flow around the nose cone at a hypersonic flow regime, and the study comprehensively examined the impact of the jet position on the shock interactions and cooling mechanism of the spike and nose cone. The results specify that injecting the tip of the spike with a multiple-row disk is more effective in protecting the blunt body from thermal damage at hypersonic flow. Moreover, a comparison between single and equivalent multiple-jet systems revealed that the thermal performance of the multi-jet configuration is significantly superior to that of a single jet.